Social Boycott as a Form of Solidarity: An Analysis from the Perspective of Hadith - muhammad farhan; Muhajirin; Sulaiman Mohammad Nur (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
This research originated from the widespread practice of the community boycotting a product suspected of supporting Israel's colonization of Palestine. The main focus of this research is the social dynamics and interpretations of hadiths regarding the boycott, allowing the topic to be examined in terms of how hadiths or religious teachings can influence the understanding and motivation behind the boycott action, or vice versa. Thus, it can stimulate or shape boycott practices as a response to social or economic issues, resisting against colonial forces. This study employs a qualitative method, specifically Ma'anil hadith. The findings reveal that this solidarity hadith can serve as a reference to create unity among individuals and groups, thereby triggering an impetus or motivation to support a common goal.